What Are the Chances of Resilon to Dominate the Market Filling Materials for Endodontics? - Dobrzańska, Joanna; Dobrzański, Lech B.; Dobrzański, Leszek A.; Dobrzańska-Danikiewicz, Anna D.; Gołombek, Klaudiusz (Metals (Basel ), 2021)
This paper is a literature review with additional virtual analyses of the authors’ own experimental research results. Knowledge from various areas was synergistically combined, appropriately for concurrent engineering, presenting several possible methodological approaches used in research, optimizing the selection of engineering materials and the conditions of their application with particular application in endodontics. Particular attention was paid to the theoretical aspects of filling material strengths, weaknesses, opportunities, and threats SWOT analysis. Attention was paid to the original concepts of Sustainable Dentistry Development in conjunction with Dentistry 4.0, which includes endodontics as an important element. The dentists’ actions, among others, in conservative dentistry, along with endodontics, requires close cooperation with engineers and the enginering sciences. Methods of root canal preparation were described, together with selected tools, including those made of nitinol. Principles concerning the process of cleaning and shaping the pulp complex are presented. The importance of obturation methods, including the Thermo-Hydraulic-Condensation THC technique, and the selection of filling materials with the necessary sealants for the success of endodontic treatment are discussed. The experimental studies were carried out in vitro on human teeth removed for medical reasons, except for caries, for which two groups of 16 teeth were separated. After the root canal was prepared, it was filled with studs and pellets of a filling material based on polyester materials, which has gained the common trade name of resilon or, less frequently, RealSeal (SybronEndo) with an epiphany sealant. The teeth for the first group were obturated by cold lateral condensation. In the second case the obturation was performed using the Thermo-Hydraulic-Condensation technique using System B and Obtura III. The experimental leakage testing was done using a scanning electron microscope SEM and a light stereoscopic microscope LSM, as typical research tools used in materialography. The research results, in a confrontation with the data taken from the literature studies, do not indicate the domination of resilon in endodontics.